Tourism in Peripheries: Perspectives from the Far North and South - Müller, Dieter K (CABI, 2014)
The ambition of this chapter is to review some of the ideas and issues that have been forwarded regarding peripheries and tourism development. The focus is on peripheries within the developed world and specifically on areas featuring a cold climate. There have been several previous attempts at defining and understanding tourism in peripheries (e.g. Hall and Johnston, 1995; Price, 1996; Butler et al., 1998; Brown and Hall, 2000) and, hence, this chapter does not aim at providing a comprehensive review of previous writings (see instead Hall, this volume, Chapter 2). Instead, it addresses a selection of issues that appear to be important restrictions in the conversion of the periphery into a pleasure periphery. Finally, this chapter outlines the contents of this book